Assessing emerging issues. The external and internal approach. (October 2015) - Carbonell, Javier; Sánchez-Esguevillas, Antonio; Carro, Belén
Highlights: There is not a one fits all approach to link emerging issues and weak signals. Igor Ansoff's categorization of weak signals is not too decisive, as the level of concretion of a weak signal is not always related with its relevance. Emerging issues cannot be identified by one weak signal but by a structure of signals. The strength of a signal in Internet media (number of hits in searches) is not relevant but the growth rate is useful. Signals must be interpreted and methods like CLA give a framework to look inside emerging issues. CLA can be useful to identify drivers that lead an emerging issue to become a trend and to identify common causal factors between different emerging issues. It also allows to highlight contradictions between stakeholders. Abstract: This article analyses emerging issues trying to find elements to assess the possibility that they become a relevant trend in the future using a twofold perspective for that purpose. On the one hand it considers the external approach, that is, the analysis of visible signals linked to the emerging issues that in an early stage are called "weak signals". On the other hand, it tries to study emerging issues taking into account their internal motivations. In this case the aim is to value the social, economic or other kind of reasons that are hidden under emerging issues. A post-structuralism perspective (CLA, causal layered analysis) is used to address this objective. This double approach allows to consider emerging issues in a holistic way, taking into account what is visible and what is not so apparent. In order to offer conclusions and results a real use case is included analyzing the emerging issues showed in the report "Informe de la Sociedad de la Información 2013" (one of the references about information society situation and ICT trends in Spain).